The Effect of Other Comprehensive Income Measurement, Free Cash Flow and Audit Tenure on Earnings Management - Munauwarah; sri firman hastuti, Cut; Mahdani, Said (Institut Bisnis dan Informatika Kesatuan, 2024)
This study evaluates the impact of other comprehensive income, free cash flow, and audit tenure on earnings management in manufacturing companies within the food and beverage subsector listed on the Indonesia Stock Exchange. The study population consists of 30 companies, with a sample of 16 companies that consistently published financial statements from 2019 to 2023. The data analysis method used is multiple linear regression, with the assistance of SPSS version 29. The results of the study show that the variables of other comprehensive income and audit tenure do not have a significant effect on earnings management. On the other hand, free cash flow is found to have a significant effect on earnings management. These findings provide insights for companies and related parties to pay more attention to free cash flow as an important indicator in managing earnings. The conclusion of this study indicates that free cash flow plays a more critical role in influencing earnings management compared to other comprehensive income and audit tenure.